The great emptiness at the beginning of the Universe - Wetterich, Christof (Physics letters, 2021)
The great emptiness is a possible beginning of the Universe in the infinite past of physical time. For the epoch of great emptiness particles are extremely rare and effectively massless. Only expectation values of fields and average fluctuations characterize the lightlike vacuum of this empty Universe. The physical content of the early stages of standard inflationary cosmological models is the lightlike vacuum. Towards the beginning, the Universe is almost scale invariant. This is best seen by an appropriate choice of the metric field - the primordial flat frame - for which the beginning of a homogeneous metric is flat Minkowski space. We suggest that our observed inhomogeneous Universe can evolve from the lightlike vacuum in the infinite past, and therefore can have lasted eternally. Then no physical big bang singularity is present.
Available online 11 May 2021
Gesehen am 14.07.2021